2022
DOI: 10.3390/biology11040604
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity Trends in the Cultivated Potato: A Spatiotemporal Overview

Abstract: We investigated the changes in genetic diversity over time and space of the cultivated potato (Solanum tuberosum L.) for the period pre-1800 to 2021. A substantial panel of 1219 potato varieties, belonging to different spatiotemporal groups, was examined using a set of 35 microsatellite markers (SSR). Genotypic data covering a total of 407 alleles was analyzed using both self-organizing map (SOM) and discriminant analysis of principal components (DAPC) de novo and a priori clustering methods, respectively. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…The evolutionary analyses of this landscape would substantially promote and accelerate the search for the variation sought after by both evolution researchers and breeders [ 65 ]. This context helps elucidate the evolution of Rpi genes, assess their present diversity, and grasp the prospects to discover new beneficial alleles both in genetic collections of wild species [ 10 , 25 , 66 ] and in already existing multi-parent hybrids, which accumulated germplasm from numerous wild species introgressed sometimes many years ago [ 52 ].…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…The evolutionary analyses of this landscape would substantially promote and accelerate the search for the variation sought after by both evolution researchers and breeders [ 65 ]. This context helps elucidate the evolution of Rpi genes, assess their present diversity, and grasp the prospects to discover new beneficial alleles both in genetic collections of wild species [ 10 , 25 , 66 ] and in already existing multi-parent hybrids, which accumulated germplasm from numerous wild species introgressed sometimes many years ago [ 52 ].…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…The approach used in this investigation based on the 22 SSR markers (Ghislain et al, 2004) enables merging the data with the named genebanks around the world. It could also be useful for the study of the belonging to different spatiotemporal groups, as done by Spanoghe et al (2022) by examining a substantial panel of 1219 potato varieties using 35 microsatellite markers (SSR) to evaluate the genetic diversity. Ghislain et al (2009) developed a potato genetic identification kit to differentiate 93.5% and 98.8% of 742 landraces using 24 and 51 SSR markers, respectively, indicating that SSR markers could efficiently identify potato germplasm at the genetic level.…”
Section: Discussionmentioning
confidence: 99%
“…The approach used in this investigation based on the 22 SSR markers ( Ghislain et al., 2004 ) enables merging the data with the named genebanks around the world. It could also be useful for the study of the belonging to different spatiotemporal groups, as done by Spanoghe et al. (2022) by examining a substantial panel of 1219 potato varieties using 35 microsatellite markers (SSR) to evaluate the genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Chiloé is one of the origin centres of the potato, its inhabitants have developed and perfected the crop and today there are more than 200 varieties [59]. However, in recent years the farmers of Chiloé have concentrated on the production of a few commercial varieties to achieve a better yield, so that today the native potato shows little genetic renewal and a loss of productive potential [60]. During fieldwork, it was observed that conventional agriculture concentrates more on commercial varieties to achieve better yields, while agroecological agriculture promotes diversity and the cultivation of native potatoes.…”
Section: Decrease In Crop Diversitymentioning
confidence: 99%